Multisystemic Side Effects of an Indispensable Old Drug: A Case Report of Chronic Lithium Use (A Patient with Multiple Side Effects of Lithium) - Levent Demirtas; Emin Murat Akbas; Husnu Degirmenci; Ali Gurel; Eren Duzgun (Case Reports in Medicine)
Presented here is a case of long-term lithium use, with multiple emerging lithium-associated side effects. An 82-year-old woman was brought into the emergency department because of loss of consciousness. According to the physical examination and laboratory analyses, patient was diagnosed with lithium-associated hypercalcemia, hyperparathyroidism, nephrogenic diabetes insipidus (NDI), symptomatic sinus bradycardia, and thyroid dysfunction. In the literature, there is a limited number of case reports with lithium induced multiple clinical conditions. Multiple clinical manifestations due to the side effects of chronic lithium use might be seen. Health care professionals should keep in mind that lithium-related side effects might trigger or exacerbate each other. To avoid toxicity, close follow-up and clinical supervision are important for the early diagnosis and treatment of these side effects, due to the narrow therapeutic index and obscure clinical signs and symptoms of toxicity.